الصناديق الاستثمارية الوقفية وتطبيقها في المملكة العربية السعودية مشروع مقترح - راشد، سليمان بن صالح (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
This research aims to present a new “Waqf” investment project which can be applied to address the relating shortages and lack of product innovation in Waqf investment. It also discuss the issues related to the traditional Waqf investment instruments like: weak management, lack of supervision and good governance. In order to achieve this objective, the researcher will study the Shari'ah rulings that are related to Waqf, The research will also examine the processes that govern the application of Waqf Investment Funds in the Kingdom of Saudi Arabia. The researcher employs the induction approach in assessing the juristic opinions, and analytical approach to legal terms, Researchers' views. It also uses comparative approach to compare between related legal terms and Shariah rulings in Investment funds. This research has analyzed some related shari'ah rulings to the proposed project; such as: Cash Waqf, Collective Waqf, the ruling of investing Waqf fund, and as it also studied origin, types and characteristics of the Investment Funds and what distinguishes it from other investment funds. The study further considered the nature of specialized Government entities in Waqf and its related regulations in the Kingdom of Saudi Arabia. Thereafter, the research analyzed the proposed Waqf Project from both Shari'ah and Legal perspectives with more concentration on most related important Shari'ah issues and its rulings. Finally, the researcher shows that there is no prohibition in sharī'ah law and the law of Kingdom of Saudi Arabia which prevent the application Waqf investment funds Project. The researcher therefore suggested some recommendations for proper application of this project.